2011
DOI: 10.1007/s11095-011-0411-z
|View full text |Cite
|
Sign up to set email alerts
|

Lyophilization of Protein-Loaded Polyelectrolyte Microcapsules

Abstract: Lyophilization is a promising strategy towards improved stability of protein-loaded microcapsules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Comparable results were observed when CpG was incorporated into the DS particles 132. De Temmerman et al showed that these results are not altered significantly by lyophilization of antigen encapsulated DS particles, making them a promising option for an effective, storable vaccine 133. Tetanus toxoid encapsulated cross‐linked dextran particles were also able to generate well over protective levels of neutralizing antibodies 134…”
Section: Particles For Delivery Of Antigens and Adjuvants: Artificmentioning
confidence: 98%
“…Comparable results were observed when CpG was incorporated into the DS particles 132. De Temmerman et al showed that these results are not altered significantly by lyophilization of antigen encapsulated DS particles, making them a promising option for an effective, storable vaccine 133. Tetanus toxoid encapsulated cross‐linked dextran particles were also able to generate well over protective levels of neutralizing antibodies 134…”
Section: Particles For Delivery Of Antigens and Adjuvants: Artificmentioning
confidence: 98%
“…Under physiological conditions, the gradual release of the model ovalbumin lasted for 8 days, and the amount of the released protein decreased with an increase in the number of bilayers. This circumstance is important for the development of long acting vaccines [69][70][71]. During encapsulation of bovine serum albumin, the concentration of protein inside microcapsules was 100 mg/ml after formation of three to five polylysine and alginate bilayers.…”
Section: Preparation Of Protein Microparticles Via Layer By Layer Adsmentioning
confidence: 99%
“…To prepare stable drugs on the basis of protein poly electrolyte microparticles, optimum conditions were found for drying of preparations, their storage, and their subsequent resuspension without loss of the shape and integrity of particles and the biological activity of the encapsulated BAC [71].…”
Section: Outlook For Creation and Use Of Protein Polyelectrolyte Micrmentioning
confidence: 99%
See 1 more Smart Citation
“…Even the morphology of calcium carbonate particles affects the loading, while the loading and the release are relevant for pharmacological applications . Despite a large number of articles devoted to protein loading into polymer‐based multilayer capsules, there is still no full understanding of the mechanism of the protein loading. For instance, the mechanism of protein embedding by co‐synthesis is still not reported in literature.…”
Section: Introductionmentioning
confidence: 99%